Religious Moderation in Tafsir An-Nur Karya T.M. Hasbi Ash-Shiddieqy: Study of Tafsir Q.S Al-Baqarah: 143 - Fitriani Fitriani; Hamdika Hidayat Muslim; Ilham Firmansyah; Izzah Faizah Siti Rusydati Khaerani (Gunung Djati Conference Series, 2021)
This study aims to discuss the moderation of religion in An-Nur’s Interpretation by T.M. Hasbi Ash-Shiddieqy, with the focus of its study on Q.S Al-Baqarah : 143. The research method is a qualitative type through literature study, while the approach to data interpretation is humanist-progressive, namely communicating between the Al-Qur’an as a limited text by social problems of humanity, faced with humans as a context that continues without stopping following the current development of the times. This research concludes that religious moderation in An-Nur’s interpretation of Q.S Al-Baqarah : 143 is that Muslims should be the best of the other ummah in balanced balanced (moderate) way in all matters. Thus relaxing radical, extremist and puritan-based groups from committing acts of violence in the name of religion.